The imperial monetary system of mughal India - Richards, John F.; Joint Committee on South Asia. (Delhi ; New York : Oxford University Press, 1987)
Contributed papers at a conference held at the National Humanities Center, Research Triangle Park, North Carolina, 1981.
"Sponsored by the Committee on South Asia of the Social Science Research Council and American Council of Learned Societies."
Includes bibliographical references.
Keywords: Money -- India -- History -- Congresses; India -- History -- 1526-1765 -- Congresses; India -- History